Analysis of Added Value and Profitability of the Coconut Sugar Agroindustry - Nurul Aisyah Nugrahaeni; Siswanto Imam Santoso; Wiludjeng Roessali (Agribusiness Journal, 2024)
This research aims to analyze the amount of added value and level of profitability of the coconut sugar agroindustry in Kedungbenda Village, Nusawungu District, Cilacap Regency. The research method used is a survey.  The sampling method uses techniques purposive sampling with a total sample of 70 coconut sugar producers. Analysis methods using quantitative analysis include cost analysis, Hayami Method added value analysis and profitability analysis. This research shows that coconut sugar producers in Kedungbenda Village, Nusawungu District, Cilacap Regency have the characteristics of being aged 51 - 64 years, with a primary school education with a percentage of 82.86%, length of business in the range 11 - 20 years, number of trees tapped in the range 11 - 20 trees, the added value resulting from processing sap into coconut sugar is IDR 1,237.16/kg with a value-added ratio of 73.36%. The income obtained from coconut sugar production is IDR 112,000.00/day and IDR 3,472,000.00/month. The income obtained from coconut sugar production is IDR 40,947.96/day and IDR 1,269,386.76/month. The resulting profitability value was 57.63%. Test results in one sample t-test The significance value is 0.00 so the coconut sugar agro-industry in Kedungbenda Village, Nusawungu District, Cilacap Regency is worth pursuing.